Laboratory testing and antihypertensive medication adherence following initial treatment of incident, uncomplicated hypertension: A real‐world data analysis. Issue 10 (20th September 2022) - Beall, Reed F.; Leung, Alexander A.; Quinn, Amity E.; Salmon, Charleen; Scory, Tayler D.; Bresee, Lauren C.; Ronksley, Paul E.
Abstract: In this study on medication adherence among newly diagnosed patients with uncomplicated, incident hypertension, we conducted a retrospective cohort study using available administrative and laboratory data from April 1, 2012 to March 31, 2017 in Alberta, Canada to understand the extent to which baseline laboratory assessment and/or subsequent follow‐up was associated with persistence with antihypertensive therapy. We determined the frequency of baseline and follow‐up testing and compared the rates of medication persistence by patient‐, neighbourhood‐, and treatment‐related factors. Of 103 232 patients with newly diagnosed, uncomplicated hypertension who filled their first prescription within our study timeframe, 52.5% were non‐persistent within 6 months. Persistent patients were more often female and residing in neighbourhoods with higher social status (with exception to rurality). Aside from older age, the strongest predictor of persistence was performance of laboratory testing related to hypertension with an apparent effect in which higher levels of medication persistence were seen with more frequent laboratory testing. We concluded that medication persistence was far from optimal, dropping off considerably after 6 months for more than half of patients. Medication persistence is a substantial barrier to realizing the full societal benefits of antihypertensive treatment. Ongoing follow up with patients, including laboratory testing, may be a critical component of better long term treatment persistence.